The Effect of Profitability, Solvency, Liquidity, Capital Structure and Good Corporate Governance on Financial Performance in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2018-2020 Period: Pengaruh Profitabilitas, Solvabilitas, Likuiditas, Struktur Modal dan Tata Kelola Perusahaan yang Baik Terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Ningrum, Aprilia Widya; Maryanti, Eny (Indonesian Journal of Innovation Studies, 2022)
The purpose of this study was to determine the effect of profitability, solvency, liquidity, capital structure, and good corporate governance on the financial performance of manufacturing companies in the food and beverages sub-sector listed on the Indonesia Stock Exchange for the period 2018-2020. The method used in this study is a quantitative method. The sampling technique used is purposive sampling technique. The population used is food and beverages sub-sector manufacturing companies listed on the Indonesia Stock Exchange fo the 2018-2020 period, totaling 29 companies.the sample used is 17 companies. The data analysis method used is SPSS 26. The results of this study indicate that profitability has a significant positive effect on financial performance, solvency has no effect on financial performance, liquidity has no effect on financial performance, capital structure has a significant negative effect on financial performance, and good corporate governance has a significant positive effect on performance finance.